PENGARUH PEMBERIAN ABU KETEL TERHADAP SIFAT FISIK TANAH, PERTUMBUHAN DAN PRODUKSI TANAMAN TEBU PADA ULTISOL DI PABRIK GULA BONE, SULAWESI SELATAN - Kiromil Abror; Bambang Siswanto; Wani Hadi Utomo (Jurnal Tanah dan Sumberdaya Lahan, 2017)
Waste of Bone sugar factory in the form of sugarcane boiler ash has not been used optimally, yet the sugarcane boiler ash contains significant amounts of K, Ca, Mg and P.  The objective of this study was to elucidate the effects of sugarcane boiler ash on soil physical properties, and growth and yield of PSBM 901 sugarcane variety at Bone sugar Factory. Treatments tested in this study were Kontrol (Urea 300 kg ha-1, SP36 200 kg ha-1, KCL 100 kg ha-1, Dolomit 1 t ha-1) (P1),  compost 6 t ha-1 (P2),  sugarcane boiler ash 40 t ha-1 + compost 6 t ha-1 (P3), sugarcane boiler ash 40 t ha-1 (P4), sugarcane boiler ash 40 t ha-1 without K fertilizer (P5), and sugarcane boiler ash 40 t ha-1 without dolomite (P6). The results showed that the P6 treatment (P6) was able to decrease soil bulk density by of 0.8 g cm-3 and soil particle density from 2.52 g cm-3 to 2.08 g cm-3. Furthermore, the P6 treatment was also able to increase the total soil porosity to 51.1% volume and aggregate stability value from 0.8 mm to 1.2 mm. The P6 treatment was also  able to increase growth,  trunk of sugarcane,  and number of tillers sugarcane. The best value of sugarcane production was shown by the P6 treatment with the value of 51.56 t ha-1. The highest profit of Rp. 15.585.528,53.was obtained from the P5 treatment.